2010
DOI: 10.1016/j.molcel.2010.01.026
|View full text |Cite
|
Sign up to set email alerts
|

AFF4, a Component of the ELL/P-TEFb Elongation Complex and a Shared Subunit of MLL Chimeras, Can Link Transcription Elongation to Leukemia

Abstract: Chromosomal translocations involving the MLL gene are associated with infant acute lymphoblastic and mixed lineage leukemia. There are a large number of translocation partners of MLL that share very little sequence or seemingly functional similarities, however, their translocations into MLL result in the pathogenesis of leukemia. To define the molecular reason why these translocations result in the pathogenesis of leukemia, we purified several of the commonly occurring MLL chimeras. We have identified a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
683
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 525 publications
(718 citation statements)
references
References 54 publications
28
683
0
7
Order By: Relevance
“…Finally, we investigated the effect of human AFF4 on the activity of P-TEFb. AFF4 is a subunit of the super elongation complex that is recruited by mixed lineage leukaemia (MLL) proteins to activate the expression of MLL target genes [35][36][37][38] . The N-terminal 300 amino acids of AFF4 were shown to specifically interact with P-TEFb 39,40 .…”
Section: Hiv-1 Tat/tar Does Not Change P-tefb Phosphorylationsmentioning
confidence: 99%
“…Finally, we investigated the effect of human AFF4 on the activity of P-TEFb. AFF4 is a subunit of the super elongation complex that is recruited by mixed lineage leukaemia (MLL) proteins to activate the expression of MLL target genes [35][36][37][38] . The N-terminal 300 amino acids of AFF4 were shown to specifically interact with P-TEFb 39,40 .…”
Section: Hiv-1 Tat/tar Does Not Change P-tefb Phosphorylationsmentioning
confidence: 99%
“…SEC plays a role in the proper coordinated induction of Hox genes during early developmental stages and is also involved in the misregulation of Hox genes in leukemia [30][31][32][33][34]. If p53 can also interact with ELL in SEC, it may inhibit the formation of SEC as well.…”
Section: Discussionmentioning
confidence: 99%
“…12 Early studies in mice implicated AF9 in normal embryonic development possibly through regulation of HOX gene expression, 13 and recent ChIP-seq analysis revealed that AF9 is recruited to H3K9ac-enriched loci near the HOX gene cluster in cancer cells. 3 AF9 is found to associate with several nuclear complexes, most notably the SEC, [14][15][16] and separately with the histone H3K79-specific methyltransferase DOT1L. 3,17,18 DOT1L-mediated H3K79 methylation is strongly linked to active gene expression, suggesting that interaction of AF9 with DOT1L may play a role in DOT1L recruitment to gene promoters and transcriptional activation.…”
Section: Role Of the Yeats Domain Proteins In Transcriptionmentioning
confidence: 99%